Implementasi Peraturan Gubernur Dki Jakarta Nomor 10 Tahun 2015 Tentang Penataan Dan Pemberdayaan Pedagang Kaki Lima Oleh Satuan Polisi Pamong Praja Di Pasar Minggu Jakarta Selatan - Mikha Christin Yunitasari; Tjahya Supriatna; Dety Mulyati (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2023)
Pasar Minggu is one of the oldest markets in DKI Jakarta which is one of the causes of overcrowding, resulting in limited selling space. The lack of selling land has pushed some people to turn into street vendors (PKL) since the expansion of the Jakarta City area. As a result, Pasar Minggu has become an unorganized area, in this case it is contrary to DKI Jakarta Regulation Number 10 of 2015 concerning Arrangement and Empowerment of Street Vendors. This research is aqualitative research that aims to find out how the implementation, supporting and inhibiting factors and the right strategy in the arrangement and control of street vendors carried out by the Civil Service Police Unit at Sunday Market, South Jakarta. This study explains that there are 4 (four) indicators of policy implementation, namely communication, resources, disposition and bureaucratic structure. The process of collecting data using observation techniques, interviews, and documentation. The results showed that the implementation of DKI Governor Regulation Number 10 of 2015 concerning Arrangement and Empowerment of Street Vendors by the Civil Service Police Unit at Pasar Minggu, South Jakarta has not run optimally due to several factors, such as the lack of awareness of street vendors about order, not yet optimal enforcement of regulations, and lack of socialization of regulations. The strategies that can be used to improve the implementation of these regulations are improving the quality of Satpol PP human resources through education and training, conducting outreach related to structuring street vendors and optimizing Satpol PP tasks so they can work optimally.